Pas koji je voleo vozove . The Dog Who Loved Trains - Paskaljević, Goran (Centar filmskih radnih zajednica SR Srbije, 1977)
A girl named Mika, convicted for drug smuggling, escapes from the transport train. Mika dreams of going to her brother to Paris, but without money or passport she is forced to accept the help of a former stuntman who is now touring provincial towns presenting primitive rodeo shows. On the road they pick up a boy in search of his long lost dog who was trained to jump on and off trains. When the youngster realizes that the cowboy is going give up Mika to the police, he offers her a ride to Belgrade on his motorcycle. There she attempts to get a passport with money she stole from the cowboy, but her criminal friends deceive her and the boy’s bike is destroyed. In desperation, Mika tries to get rid of the affectionate boy who still wants to help her and jumps on a passing train. Trying to catch up with her, the boy injures himself and falls under the train. With the horrific scene moving further and further away from her, Mika notices the boy’s dog peacefully riding her train.